Commodifying Women in the Digital Creativity Sphere of Political Marketing Communication - Tuti Widiastuti; Edy Prihantoro; Herna Herna (Expose: Jurnal Ilmu Komunikasi, 2023)
Indonesia's 2019 presidential and vice-presidential election not only presents fierce competition among contestants, but also the creativity of political supporters during the campaign period. In addition to the emergence of the buzzer phenomenon, volunteers, producers and also distributors of hoaxes, what is interesting is the participation of mothers or adult women who take part in enlivening social media. This community, some say 'emak-emak' (connoted as an uneducated mother), some say ‘ibu bangsa’ (connoted more educated), actively campaigning for their candidates in political contestation. No wonder social media yells like 'the power of emak-emak' are very popular. This paper unfolds the phenomenon of women's political participation in Indonesia, and sees that the commodification of women into practical politics cannot yet be interpreted as a permanent exchange of use-values. On the one hand, it does provide political space for women, but on the other hand, it still does not eliminate the stereotypes of women as emotional creatures. This ambivalent participation is underrepresenting the interests of the majority of women voters. Even though it seems creative, efforts to 'revive' women in the political marketing communication space ala 'the power of emak-emak' only places women as 'decorative attributes of teasers', cheerleaders, not yet representing a central and significant role in mainstreaming Indonesian politics.